The role of the south-western Alps as a unidirectional corridor for Mediterranean brown trout (Salmo trutta complex) lineages. (2nd November 2020) - Splendiani, Andrea; Berrebi, Patrick; Tougard, Christelle; Righi, Tommaso; Reynaud, Nathalie; Fioravanti, Tatiana; Lo Conte, Paolo; Delmastro, Giovanni B; Baltieri, Marco; Ciuffardi, Luca; Candiotto, Alessandro; Sabatini, Andrea; et al.
Abstract: The role of the south-western Alps as a corridor for Mediterranean trout ( Salmo trutta complex Linnaeus, 1758) was evaluated in order to understand the influence of the last glacial events in shaping the spatial distribution of the genetic diversity of this salmonid. For this, the allochthonous hypothesis of a man-mediated French origin (19th century) of the Mediterranean trout inhabiting the Po tributaries in the Italian side of the south-western Alps was tested. A total of 412 individuals were analysed at the mitochondrial control region. The phylogenetic classification was carried out by using a Median-Joining Network analysis. Mismatch pair-wise analysis, molecular dating and Kernel density distribution analysis of the main mitochondrial lineages were evaluated to compare past demographic dynamics with the current spatial distribution of genetic diversity. The main outcomes resulted strongly in agreement with a biogeographic scenario where the south-western Alps acted as a unidirectional corridor that permitted the colonization of the upper Durance (Rhône River basin) by trout from the Po River basin. Therefore, the Mediterranean trout should be considered as native also along the Italian side of the south-western Alps and the allochthonous hypothesis should be rejected.